2018
DOI: 10.1016/j.jped.2017.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Trp64Arg polymorphism of the ADRB3 gene associated with maximal fat oxidation and LDL-C levels in non-obese adolescents

Abstract: Although the physiological processes related to lipolysis and lipid metabolism are complex, the presence of the Arg 64 allele was associated with lower rates of FATMAX during aerobic exercise, as well as with higher levels of LDL-c in adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…A correlation between Trp64Arg and type 2 diabetes, likely dependent on ethnicity, has been described in a recent meta-analysis [187]. The presence of Trp64Arg was also reported to influence metabolic parameters such as LDL-C [10] and HDL-C [11] accumulation rates and resistance to weight loss in cohorts of Brazilian and Japanese patients, respectively. Consistently, Trp64 polymorphism correlates with increases in Body Mass Index [188] and has a weak but significant influence on carriers leading to greater fat mass and percentage [189].…”
Section: Polymorphismsmentioning
confidence: 99%
See 1 more Smart Citation
“…A correlation between Trp64Arg and type 2 diabetes, likely dependent on ethnicity, has been described in a recent meta-analysis [187]. The presence of Trp64Arg was also reported to influence metabolic parameters such as LDL-C [10] and HDL-C [11] accumulation rates and resistance to weight loss in cohorts of Brazilian and Japanese patients, respectively. Consistently, Trp64 polymorphism correlates with increases in Body Mass Index [188] and has a weak but significant influence on carriers leading to greater fat mass and percentage [189].…”
Section: Polymorphismsmentioning
confidence: 99%
“…Given β 3 -AR expression and signaling in districts such as myocardium and adipose tissue, mirabegron is also being tested in repurposing trials for cardiovascular and metabolic conditions (commented on in [8,9]). Consistently, β 3 -AR’s most common genetic variant, Trp64Arg, has been found to positively correlate with metabolic parameters such as HDL-C (High Density Lipoprotein-Cholesterol) and LDL-C (Low Density Lipoprotein-Cholesterol) accumulation rates and glucose tolerance [10,11]. After a brief overview of basic information regarding gene structure, protein, and pharmacology of the receptor, we will focus on β 3 -AR role in some of the main tissues where its expression has been reported.…”
Section: Introductionmentioning
confidence: 97%
“…Most studies report a fatmax between 40% to 50% of VO 2 max in obese subjects; however, there are large intra-individual variations, independent of sex (30-65% of VO 2 max) [6,7]. Such variations are related to differences in CRF, body composition, and genotype [17,18], indicating that at moderate exercise intensity, some individuals will be working within the fatmax zone, while others are below or above, resulting in different fat oxidation rates among individuals. For these arguments, moderate exercise training should not be considered as fatmax training, as exercise at maximal fat oxidation (MFO) requires individual testing and prescription.…”
Section: Introductionmentioning
confidence: 99%
“…If the relationship between IR and Trp64Arg mutation can be attributed to obesity, we should pay attention to the underlying mechanism. The Trp64Arg variant has been shown to reduce lipolysis (47). Another study found that the Trp64Arg mutation can influence body weight loss (48).…”
Section: Discussionmentioning
confidence: 99%